LPG supply in Thailand : a case study for energy planning - Murshed, Rahman; Walter, Despiegelaere, Ir.; Mesritz, E.A.; Prida Wibulswas; Tabucanon, Mario T.; Carls Duisberg Gesellschaft (Federal Republic of Germany) (Bangkok : Asian Institute of Technology, 1982)
In the face of limited supplies of petroleum products and phenomenally high energy prices , the knowledge of economic policy impacts on demand & supply of fuel is vital to national energy planning Optimal allocation of available energy resources at minimum cost plays a significant role in the economy of any country. The study deals mainly with the formulation of an energy model ; a linear program that simulates the LPG supply in relation to Thailand' s available source ,as well as its effect on the other distillate products. It also presents an economic analysis using the model , of the LPG supply of the country by 1984. Results of the study indicate an imbalance of current product pricing such that imputation of major portion of the petroleum requirements is cheaper than local production. Substitution of gasoline , kerosene & diesel by LPG is not attractive when LPG export is possible , while. government's contribution over 1. 94 baht per kilogram of charcoal favors substitution by LPG
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1982
Keywords: Liquefied petroleum gas; Energy policy -- Thailand